Model hubungan informasi non keuangan dengan initial return dan return saham 7 hari - Basuki Toto Rahmanto; Febriansyah Febriansyah (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This study aims to determine the factors that influence the initial return and return of shares after 7 days after the initial public offering of companies that went public on the Indonesia Stock Exchange in the period 2011-2015. This research is causal design research. The data source of this research is a list of listed companies that made an initial public offering in 2011-2015 on the Indonesia Stock Exchange and a list of initial stock prices, stock prices on the first day and stock prices 7 working days after the IPO on the secondary market. As well as auditor reputation data, ownership retention, and company age. The results of the simultaneous regression analysis show that all the independent variables together affect the initial return.